Single-Center Experience Using a 3D4K Digital Operating Scope System for Aneurysm Surgery. Issue 6 (5th June 2022) - Pantel, Tobias; Drexler, Richard; Göttsche, Jennifer; Piffko, Andras; Westphal, Manfred; Regelsberger, Jan; Dührsen, Lasse
Abstract : BACKGROUND: In recent years, 3D4K exoscope systems (EXs) have been introduced to microneurosurgery and reported to be an alternative to conventional operating microscopes (OMs). This study reviews our single-center experience using an 3D4K EX in intracranial aneurysm surgery. OBJECTIVE: To investigate the applicability of a novel 3D4K EX for intracranial aneurysm surgery. METHODS: A retrospective analysis of patients who underwent microsurgical repair of incidentally or ruptured cerebral aneurysms between August 2018 and August 2020 was performed. Patient and aneurysm characteristics and technical features, including 3-dimensional indocyanine green fluorescence, were evaluated. Data on surgery duration were statically assessed for a time trend and comparability with the OM cohort. RESULTS: Overall, we collected 185 aneurysm cases in which the exoscope was used in 44 cases. The mean duration of surgery using the EX was in similar range to those using the OM (165.5 ± 45.8 minutes vs 160.5 ± 39.2 minutes, P > .05). Routine postoperative computed tomography angiography showed comparable rates of complete aneurysm occlusion (95.5% vs 92.2%, P > .05) and postoperative complications (9.1% vs 9.7%, P > .05). There was no necessity to revert to the OM from the EX. Three-dimensional indocyanine green fluorescence was used in all procedures without any malfunction. CONCLUSION: The 3D4K EX for vascular microsurgical cases proved to be as useful as the OM. Because of the ease of use and comparable surgical results, the EX has the potential to become an accepted and additional visualization tool in vascular microsurgery next to the OM.